An Introduction to USGS Topo Maps - Hartwig Hochmair; Adam Benjamin (EDIS, 2021)
Topographic maps provide both a detailed and accurate representation of cultural and natural features on the ground and a quantitative representation of relief, usually using contour lines. They can be used to address spatial questions in disciplines related to natural resources, hydrology, forestry, agriculture, or ecology. In 1879, the United States Geological Survey began to map the topography of the United States, producing new map versions of each area at semi-regular time intervals. US Topo maps are the current generation of USGS topographic maps. Unlike traditional topographic maps, the US Topo product is automatically generated from national map databases with topographic maps and produced every three years for all 48 of the contiguous United States, Hawaii, and the United States territories. They are published as freely available geospatial PDF documents that facilitate coordinate readings and spatial measurements (e.g. distance, area) through built-in georeferencing technology. This 7-page fact sheet written by Hartwig H. Hochmair and Adam R. Benjamin and published by the UF/IFAS School of Forest Resources and Conservation focuses on US Topo quadrangle download procedures and layer structure. https://edis.ifas.ufl.edu/fr432